First record of Latrodectus hesperus Chamberlin & Ivie, 1935, Western Black Widow (Araneae, Theridiidae), in Slovakia - Pavol Purgat; Lucia Švecová (Check List)
An alien spider species, Latrodectus hesperus Chamberlin & Ivie, 1935, is reported from Slovakia for the first time. The spider was accidentally transported to northern Slovakia with goods, and it was found in synanthropic habitat. This record confirms the route through which spiders of the genus Latrodectus are imported into Europe. Characteristic features, along with photographs of the habitus and copulatory organs, are presented.